Analisis Pengaruh Jumlah Penduduk, Pertumbuhan Ekonomi, Dan Industri Kecil Terhadap Penyerapan Tenaga Kerja Di Kabupaten Pacitan - Irma Berliana Chandra Dewi; Syamsul Huda; Putra Perdana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Increased economic activities, such as production, distribution, and consumption of goods, contribute to economic growth. It is anticipated that a rise in the production of products and services will enhance people's welfare by creating more jobs, bringing in more money, and meeting more needs. In the context of production, labour or workers are not just an element, but a crucial component at every stage. The role of labour is not only limited to the firm level, but has significant potential to contribute to the overall development of a country. This study tries to find out how labour absorption in Pacitan Regency is affected by several factors such as population growth, economic expansion, and the number of small businesses. The researchers applied quantitative techniques. Secondary data from relevant institutions was collected for this study and then reprocessed. The Central Bureau of Statistics of Pacitan Regency is such an institution. The data analysis technique used in this study is multiple linear regression analysis. This research uses SPSS formulas and applications to fulfil certain requirements, which helps to understand the relationship between factors through numerical data. The findings show that labour absorption in Pacitan Regency is positively and significantly influenced by economic growth and the number of small industries. Meanwhile, the labour absorption variable is positively and marginally influenced by the number of population. Keywords: economic growth, population, small industry